Patellofemoral Instability in Active Adolescents - Ries, Zachary; Bollier, Matthew (The Journal of Knee Surgery, 2015)
Patellofemoral instability is a common problem in the adolescent population. Patellar stability depends on a dynamic interplay between bony and soft tissue restraints. Several pathoanatomical factors increase the likelihood of patellar instability: patella alta, trochlear dysplasia, malalignment, and deficient proximal medial restraints. Treatment for first-time patella dislocations is typically nonoperative and includes bracing, early range of motion, and physical therapy. The only absolute indication for early surgery is a large osteochondral fragment that can be fixed. Surgical stabilization is indicated for chronic patellar instability and includes both proximal and distal realignment options. Medial patellofemoral ligament reconstruction is the treatment of choice in most adolescent patients with patella instability. Distal bony realignment procedures are reserved for skeletally mature adolescents.
Keywords: patellofemoral; instability; adolescent; MPFL